دور استراتيجيات التصنيع الأخضر في تعزيز التنمية المستدامة : دراسة استطلاعية لآراء عينة من المدراء في الشركة العامة لصناعة الادوية و المستلزمات الطبية في نينوى - د. محمد عبدالوهاب العزاوي; اسراء وعدالله السبعاوي (PROSPECTIVE RESEARCHES, 2023)
The research seeks to define the role of green manufacturing strategies in enhancing sustainable development. The green manufacturing concept is one of productivity concepts that have emerged newly as a result of the urgent need to preserve the environment and to take the necessary measures for it. It becomes necessary to look for an effective production system which produces goods and services, and at the same time, ensures environmental conservation. In general, the research tries to answer the questions related to the existence of perceptions about the concept of green manufacturing? The importance of green manufacturing and the most important strategies applied in this area, on one hand, and the concept of sustainable development, on the other hand, in the organization in question, as well as how to promote sustainable development through the implementation of strategies for green manufacturing in the organization under research in the future. The hypotheses have been tested by a set of statistical methods and through the statistical analysis SPSS. Also, questionnaire is used as a basic tool to collect required data and information. The research comes up with a set of conclusions. The most important one is the existence of correlation and significant impact relations between green manufacturing strategies and sustainable development. In the light of the conclusions reached by the researchers, a set of recommendations are suggested, the important is the need to realize the importance of green manufacturing strategies as well as the possession of perceptions and visions concerning them and their effects in the organizational aspects.